Gender Differences in Burnout Among Endocrinologists in China - Wang, Jing; Zhang, Lufa; Jiang, Feng; Liu, Yuanli; Wang, Mingxiao; Wu, Yinuo; Tang, Yi-Lang (Frontiers in Psychology, 2022)
Objective To survey the prevalence of burnout in a national sample of endocrinologists in China and to examine its correlates, with a special focus on gender differences. Methods An anonymous online survey was conducted among endocrinologists in 31 provincial government-owned “People’s Hospitals” of each province in mainland China. Demographic and work-related factors were collected from participants. The Maslach Burnout Inventory-Human Services Survey (MBI-HSS) was used to assess burnout, including emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (PA). Results A total of 711 endocrinologists (72.1% were female and mean age was 39.63 ± 8.51 years old) completed the survey. Burnout was reported by 32.8% of the participants. There were no significant gender differences in the overall prevalence of burnout or EE, DP, and PA (all p > 0.05). A multi-level linear regression revealed: (1) In male participants, PA was significantly associated with age (β = 0.03, p = 0.003), DP was inversely associated with age (β = −0.06, p = 0.005), EE was significantly associated with shorter sleep duration (β = −0.25, p = 0.006), and longer work hours (β = 0.01, p = 0.016). (2) In females, PA was significantly associated with age (β = 0.01, p = 0.038), EE and DP were both significantly associated with shorter sleep duration (β = −0.19, p = 0.001; and β = −0.15, p = 0.011, respectively). EE and DP were also associated with work hours (β = 0.02, p < 0.001; and β = 0.01, p < 0.001, respectively). Conclusion Nearly one-third of endocrinologists in China experienced burnout. Although there were no significant gender differences in the prevalence of overall burnout or EE, DP, and PA scores, male and female participants differed in factors associated with EE, DP, and PA. Interventions need to be tailored to target different aspects in male and female endocrinologists and target different subgroups.